If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 65 = 2x + 45 Reorder the terms: 65 + 7x = 2x + 45 Reorder the terms: 65 + 7x = 45 + 2x Solving 65 + 7x = 45 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 65 + 7x + -2x = 45 + 2x + -2x Combine like terms: 7x + -2x = 5x 65 + 5x = 45 + 2x + -2x Combine like terms: 2x + -2x = 0 65 + 5x = 45 + 0 65 + 5x = 45 Add '-65' to each side of the equation. 65 + -65 + 5x = 45 + -65 Combine like terms: 65 + -65 = 0 0 + 5x = 45 + -65 5x = 45 + -65 Combine like terms: 45 + -65 = -20 5x = -20 Divide each side by '5'. x = -4 Simplifying x = -4
| (n-5)(8n-7)=0 | | x=1.3 | | 13x-41=180 | | 7(4y-5)+3(4y+6)= | | 8n^2-80n+200=0 | | -x/3=x/3+52 | | 5x/7=x/7+644 | | (7p-9)(9p+5)=0 | | 60=12+6(n-1) | | 2x(x-4)=-14x+8 | | 6x+27+3x+54=180 | | -17-5p=5(2+4p)+2p | | -58.75-x/8=7x/8+191.25 | | 14b-13b+3b=20 | | u(6u-7)=0 | | 4ln(7x)=16 | | -17-5p=5(2+4)+2p | | 3x^3-2x^2-12x+18=0 | | 6w+5w-9w=12 | | 5y(y+2)=0 | | 2tanx+7=3 | | 6+2x-5=6-3(2x-1) | | 10h-8h+h-3h+h=7 | | 5+3(x+4)=-(2x-1)-9 | | log[4](13*7)= | | 5r^2-10r-15=0 | | 2x^3+13x=8x^2 | | -17-55p=5(2+4p)+2p | | 20-2=38 | | -3(x-4)+2xy=xy-5x+xy-6 | | 2w^2-22w+48=0 | | 5(2)-2=38 |